Perdebatan dan Argumentasi Semua Agama adalah Islam - Nanang Tahqiq (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2012)
This paper will elaborate the conceptions and meanings of Islam, both etymologic-ally and terminologically as well, through historical and doctrinal-theological perspectives respectively. Even though, Islam, terminologically, denotes the Prophet’s religion and a formal system fetched and assembled by the Prophet Muhammad—as narrated by the two well-known Prophetic sayings (Hadīth)—however, according to the Qur’ān, it (islām, with small letter /i/) signifies ‘to surrender.’ Within such Qur’ānic context, the word islām is not exclusively referred to the community or for the believers of Muhammad’s sharī‘a per se. In the course of Muslim history, the word and meaning of islām are believed being an institution. Yet, to examine the Qur’ān, the article will acquire lots of the Qur’ānic verses conveying such word and meaning of true islām in the function of ‘religion of resignation.’ As such, islām is actually the religion belonging to the whole prophets and apostles who taught a total capitulation to God. Moreover, islām connotes submission of personal quality as a person to God, whatever religion and belief he embraces. However, in addition, Islam cannot remain lonesome by itself, unless is being associated with īmān (belief, faith) and ihsān (God’s omnipresent.)